2007
DOI: 10.1103/physrevlett.99.167204
|View full text |Cite
|
Sign up to set email alerts
|

Topological Estimator of Block Entanglement for Heisenberg Antiferromagnets

Abstract: We introduce a computable estimator of block entanglement entropy for many-body spin systems admitting total singlet ground states. Building on a simple geometrical interpretation of entanglement entropy of the so-called valence bond states, this estimator is defined as the average number of common singlets to two subsystems of spins. We show that our estimator possesses the characteristic scaling properties of the block entanglement entropy in critical and noncritical one-dimensional Heisenberg systems. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…On the other hand the SU(2) singlet basis is not orthogonal. However it might happen that in the basis of SU(2) singlets, the coefficients appearing in the wavefunction are non-negative real numbers which through a proper normalisation can be interpreted as probabilities [7,8]. One can then consider the problem of shared information in the wavefunction as if it were the PDF of a stationary state of a stochastic process.…”
Section: Estimators Of Shared Information For Dyck Paths Configurationsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand the SU(2) singlet basis is not orthogonal. However it might happen that in the basis of SU(2) singlets, the coefficients appearing in the wavefunction are non-negative real numbers which through a proper normalisation can be interpreted as probabilities [7,8]. One can then consider the problem of shared information in the wavefunction as if it were the PDF of a stationary state of a stochastic process.…”
Section: Estimators Of Shared Information For Dyck Paths Configurationsmentioning
confidence: 99%
“…This estimator was introduced independently by Chhajiany et al [7] and Alet et al [8] in the context of SU(2) symmetric spin 1/2 quantum chains, and further studied by Jacobsen and Saleur [19]. The aim was to measure the average number of link (SU(2) singlets) crossings at a given site of the quantum chain.…”
Section: Estimators Of Shared Information For Dyck Paths Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such quantity is the valence bond (VB) entanglement entropy for SU(2) quantum spin systems [134,135], which generalizes the idea, first used in the context of random spin chains [79,92,93], that for a pure valence bond state whose wave function is a product of disjoint singlet bonds between two spin-1/2s the entanglement entropy of a subsystem is essentially the number of singlet bonds that cross the boundary between the subsystem and the remainder of the system, with each singlet |Ψ s = (|↑ A ↓ B − |↓ A ↑ B )/ √ 2 contributing ln 2 to the entanglement entropy. For more general wave functions which are superpositions of pure VB states the number of such crossings can be averaged to obtain a well-defined (with certain restrictions [134]) measure of entanglement.…”
Section: Concluding Remarks On Bipartite Fluctuations a Comparismentioning
confidence: 99%
“…In an interesting recent paper [10] (see also [11] for a related, independent work) it was suggested that, even when |Ω is not a single valence bond state but a superposition of such states, the average number of singlets N c (Ω) crossing the boundary of the subsystem (multiplied e.g. by ln 2 for spins 1/2) could still be used as a measure of the entanglement entropy with all the required qualitative properties.…”
mentioning
confidence: 99%